Perilaku Disjunction Perawat Rumah Sakit Medika Permata Hijau Jakarta (Journal of Hospital Management, 2020)
The issue of turnover is unavoidable and very detrimental to the hospital because a lot of costs have been spent on employee recruitment and training. Turnover is inevitable, even if the organization is fully committed to creating a conducive work environment.The purpose of this study is to provide empirical evidence that there is a simultaneous process of the influence of workload, burnout, and job satisfaction, on Tunover Intention.The research design used is quantitative with the type of hypothesis testing. This type of research is causality. The unit of analysis is the nurse. The time horizon is a one shot study. Data analysis using path analysis with multiple regression.The results showed that Burnout, Workload, and Job Satisfaction had a significant positive effect on Turnover Intention. Burnout has a significant positive effect on Job Satisfaction, Workload has a significant positive effect on Job Satisfaction. Burnout has a significant positive effect on Turnover Intention. Workload does not have a positive effect on Turnover Intention. Job Satisfaction has a significant positive effect on Turnover Intention.The research findings show that nurses at MPH Hospital behave disjunction by behaving waiting to get better opportunities in the future in the intention to change tasks.Keyword: Burnout, Workload, Turnover Intention, Job Satisfaction